Don't Leave Without Them: Dispensing asthma medications to pediatric patients upon discharge is associated with decreased hospital readmissions - Aleda M.H. Chen, Pharm.D.,M.S., Ph.D; Kristen Lamberjack, Pharm.D; Thaddeus Franz, Pharm.D; Kelly J. Hiteshew, Pharm.D (University of Minnesota Libraries Publishing, 2012)
Purpose: Asthma exacerbations are a leading cause of hospital and emergency department admissions at pediatric institutions. The objective of this study was to determine if patients who obtain discharge medications from a pediatric institution's outpatient pharmacy after an admission for asthma have a lower thirty-day readmission rate than those who do not obtain discharge medications from the outpatient pharmacy. Methods: This multi-phase retrospective study included an initial chart review, an intervention period, and a second chart review of the intervention period. The chart reviews included patients ages two years and older with a discharge diagnosis of asthma or wheezing. During the intervention phase, pharmacists promoted use of the outpatient pharmacy by patients admitted for these conditions using multiple methods. In each chart review, the patients readmitted for asthma or wheezing within thirty days were classified as either outpatient pharmacy users (OPP users) or non-OPP users. Differences in readmission rates between OPP users and non-OPP users, as well as differences in overall OPP utilization, were analyzed before and during the intervention phase using a Chi-square test. Results: The initial chart review found no significant difference in thirty day readmission rates between OPP users and non-OPP users (6.2% and 7.5%, respectively; χ2 = 1.15; p = 0.274). The number of OPP users increased significantly from the first chart review to the second (11.8% and 45.9%, respectively; χ2 = 929.04, p < 0.001). The second chart review revealed that OPP users had a significantly lower readmission rate than non-OPP users during the intervention phase (2.3% and 10.9%, respectively; χ2 = 52.5; p < 0.001). Conclusion: Obtaining discharge medications from the OPP was associated with a lower thirty-day readmission rate in children with asthma. Promoting use of the OPP for transitional care should continue to be part of future efforts to decrease hospital readmissions.